Prove using the principle of mathematical induction: (i) The number of diagonals of a convex polygon with n vertices is n(n − 3)/2, for n ≥ 4, (ii) 2n < n! for for all n > k > 0, discover the value of k before doing induction.

Respuesta :

Step-by-step explanation:

Proof for i)

We will prove by mathematical induction that, for every natural [tex]n\geq 4[/tex], the number of diagonals of a convex polygon with n vertices is [tex]\frac{n(n-3)}{2}[/tex].

In this proof we will use the expression d(n) to denote the number of diagonals of a convex polygon with n vertices

Base case:

First, observe that:, for n=4, the number of diagonals is

[tex]2=\frac{n(n-3)}{2}[/tex]

Inductive hypothesis:  

Given a natural [tex]n \geq 4[/tex],

[tex]d(n)=\frac{n(n-3)}{2}[/tex]

Now, we will assume the induction hypothesis and then use this assumption, involving n, to prove the statement for n + 1.

Inductive step:

Observe that, given a convex polygon with n vertices, wich we will denote by P(n), if we add a new vertix (transforming P(n) into a convex polygon with n+1 vertices, wich we will denote by P(n+1)) we have that:

  • Every diagonal in P(n) will still be a diagonal in P(n+1).
  • One (and only one) side of P(n) will be a diagonal in P(n+1).
  • There would be an extra n-2 diagonals (those that connect with the new added vertix).

Because of these observation we know that, for every [tex]n\geq 4[/tex],

[tex]d(n+1)=d(n)+1+(n-2)=d(n)+n-1[/tex]

Therefore:

[tex]d(n+1)=d(n)+n-1=\frac{n(n-3)}{2}+n-1=\frac{n^2-3n+2n-2}{2}=\frac{n^2-n-2}{2}=\frac{(n+1)(n-2)}{2}[/tex]

With this we have proved our statement to be true for n+1.    

In conlusion, for every natural [tex]n \geq 4[/tex],

[tex]d(n)=\frac{n(n-3)}{2}[/tex]

Proof for ii)

Observe that:

  • For n=1 [tex]2n=2>1=n![/tex]
  • For n=2 [tex]2n=4>2=n![/tex]
  • For n=3 [tex]2n=6=n![/tex]

Then, the statement is not true for n=1,2,3.

We will prove by mathematical induction that, for every natural [tex]n \geq 4[/tex],

[tex]2n<n![/tex].

Base case:

For n=4, [tex]2n=8<24=n![/tex]

Inductive hypothesis:  

Given a natural [tex]n \geq 4[/tex], [tex]2n<n![/tex]

Now, we will assume the induction hypothesis and then use this assumption, involving n, to prove the statement for n + 1.

Inductive step:

Observe that,

[tex]n!+2\leq (n+1)! \iff n!+2\leq n!(n+1) \iff 1+\frac{2}{n!}\leq n+1 \iff 2\leq n*n![/tex]

wich is true as we are assuming [tex]n\geq 4[/tex]. Therefore:

[tex]2(n+1)=2n+2<n!+2\leq (n+1)![/tex]

With this we have proved our statement to be true for n+1.    

In conlusion, for every natural [tex]n \geq 4[/tex],

[tex]2n<n![/tex]